Quality and content assessment of internet information on nasoalveolar molding - Merve Nur Eglenen; Can Arslan; Derya Germec Cakan (BMC Public Health)
Abstract Background To evaluate the quality and content of websites related to nasoalveolar molding (NAM). Methods A systematic Internet search was conducted using the keywords “nasoalveolar molding” and “presurgical nasoalveolar molding” determined through Google Trends and popular search engines: GoogleTM, YAHOO!® and Yandex®. The top 50 websites were evaluated for each keyword and search engine. Repetitive websites, advertisements, scientific articles, and irrelevant websites were excluded from the study. The remaining 40 websites were evaluated using JAMA benchmarks, HON criteria, DISCERN, and EQIP tools. Results 75% of websites were created for informational purposes, and the remaining websites were created for clinical promotion and advertising. According to DISCERN, only 2.5% of the sites were classified as excellent (63 points): 7.5% very weak (16–26 points), 22.5% weak (27–38 points), 40% moderate (39–50 points), and 27.5% good (51 points-62 points). Conclusions Internet information on NAM was generally at a moderate to poor level in terms of quality and content. In this regard, patients should be informed about the limits of their Internet information, and the Internet content that patients can obtain information should be increased.